The Effect of Multilayer Gold Nanoparticles on the Electrochemical Response of Ammonium Ion Biosensor Based on Alanine Dehydrogenase Enzyme - Ling, TL; Ahmad, M; Heng, LY; Seng, TC (Hindawi Ltd, 2024)
The use of multilayer of gold nanoparticles (AuNPs) attached on gold electrode surface via thiol chemistry to fabricate an ammonium (NH4+) ion biosensor based on alanine dehydrogenase (AlaDH) was investigated. The approach of the study was based on construction of biosensor by direct deposition of AuNPs and 1,8-octanedithiol (C8-DT) onto the gold electrode surface. For the immobilisation of enzyme, 2-mercaptoethanol (2BME) was first covalently attached to AlaDH via esther bonding and then followed by chemically attached the 2BME-modified AlaDH (2BME-AlaDH) moiety onto the AuNPs electrode via the exposed thiol group of 2BME. The resulting biosensor response was examined by means of amperometry for the quantification of NH4+ ion. In the absence of enzyme attachment, the use of three layers of AuNPs was found to improve the electrochemistry of the gold electrode when compared with no AuNPs was coated. However, when more than three layers of AuNPs were coated, the electrode response deteriorated due to excessive deposition of C8-DT. When AlaDH was incoporated into the AuNPs modified electrode, a linear response to NH4+ ion over the concentration range of 0.1-0.5 mM with a detection limit of 0.01 mM was obtained. In the absence of AuNPs, the NH4+ ion biosensor did not exhibit any good linear response range although the current response was observed to be higher. This work demonstrated that the incorporation of AuNPs could lead to the detection of higher NH4+ ion concentration without the need of dilution for high NH4+ ion concentration samples with a rapid response time of < 1 min.